2015
DOI: 10.1007/s00114-015-1284-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the staminode in a representative sample of Scrophularia and its role as nectar safeguard in three widespread species

Abstract: Approximately 30% of the genera of Scrophulariaceae s.str. have a staminode, which is the remnant of a sterile stamen. However, there are no studies of the functionality or evolutionary pattern of staminodes in that family. This paper investigates three Scrophularia species with different staminode sizes to determine if the staminode safeguards nectar from dilution by rainwater and if it influences pollinator behavior. We also study staminode evolution and ancestral state reconstruction onto a phylogeny contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Staminodes are common floral structures that help both to attract visitors and to protect the sex organs [20,29], but our observations found that visitors of D. caeruleum contacted the anthers and stigmatic surface by opening the door-like structure of the staminodes. A considerable number of plant species are known, e.g., members of genera such as Salvia, Cornus, Calceolaria, etc., where flowers have movable parts, which are obstacles that must be actively moved by a visitor to access the flower rewards and achieve pollination [12,26].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Staminodes are common floral structures that help both to attract visitors and to protect the sex organs [20,29], but our observations found that visitors of D. caeruleum contacted the anthers and stigmatic surface by opening the door-like structure of the staminodes. A considerable number of plant species are known, e.g., members of genera such as Salvia, Cornus, Calceolaria, etc., where flowers have movable parts, which are obstacles that must be actively moved by a visitor to access the flower rewards and achieve pollination [12,26].…”
Section: Discussionmentioning
confidence: 66%
“…Recent studies have found that staminodes form physical barrier structures in some plant species and could play several different functional roles. The staminode of the three Scrophularia species (S. lyrata, S. scorodonia, and S. canina) flowers, for example, is found to protect the nectar from dilution by rainwater [20]. Such staminodes may also perform the function of insect screening.…”
Section: Introductionmentioning
confidence: 99%
“…During seven years of molecular phylogenetic analyses of Scrophularieae taxa, from the beginning of 2011 to the end of 2017, 12 studies have been published, which cover three genera of the tribe Scrophularieae and address question at generic level (Scheunert & Heubl 2011, 2014, Attar et al 2011, Navarro-Pérez et al 2013, Ghahremaninejad et al 2015, Rodríguez-Riaño et al 2015, Sotoodeh 2015, Valtueña et al 2016, Chen et al 2017). All studies have used only sequence data as the marker in assessing phylogenetic relationships in the Scrophularieae.…”
Section: Type Of Molecular Datamentioning
confidence: 99%
“…When compared with other single copy protein coding genes, nuclear rRNA genes are routinely amplified due to their small size associated to the availability of highly conserved flanking sequences and easy to detect even from small quantities of DNA because of the high copy number of the rRNA clusters. Based on these technical advantages, ribosomal genes are among the first sequences that have been extensively exploited in phylogenetic analyses of the tribe Scrophularieae (Scheunert & Heubl 2011, 2014, Attar et al 2011, Navarro-Pérez et al 2013, Ghahremaninejad et al 2015, Rodríguez-Riaño et al 2015, Sotoodeh 2015, Valtueña et al 2016, Chen et al 2017.…”
Section: Type Of Molecular Datamentioning
confidence: 99%
See 1 more Smart Citation